AGRICULTURAL INPUT CREDIT AND THE ADOPTION OF SUSTAINABLE AGRICULTURAL PRACTICES (SAPS) IN SELECTED SUB-SAHARAN AFRICA (SSA) COUNTRIES: AN ENDOGENOUS POISSON REGRESSION APPROACH - Donkoh, S. A. (UDS International Journal of Development, 2019)
Smallholder farmers, mostly in sub-Saharan Africa (SSA), are the hardest hit by climate change impacts because of their over reliance on rainfall and other natural factors. This has led to the development and extension of a number of improved agricultural technologies and practices, otherwise known as sustainable agricultural practices (SAPs). The question that is often asked is whether or not agricultural credit can improve the adoption of SAPs. The objective of this study was to investigate the factors influencing access to agricultural credit and the effects on the adoption of SAPs in selected SSA countries. The Intensification of food crops agriculture in sub-Saharan Africa (AFRINT II) data set were used for the study. The sample involved about 3,000 households from nine African countries, namely; Ethiopia, Ghana, Kenya, Malawi, Nigeria, Tanzania, Uganda, Zambia and Mozambque. A Poisson regression with endogenous treatment effect was estimated to address a possible selectivity bias. In all, 47.5% of the respondents, as against 52.5%, had access to credit. The commonest technologies adopted were intercropping, integrated nutrient management, crop rotation and soil and water conservation. The estimation results suggest that access to credit and formal education as well as land ownership lead to the adoption of SAPs. However, while group membership facilitates access to credit, households headed by relatively old farmers have lower probability of accessing credit than those headed by the young. Both government institutions and the private sector must work at upscaling credit supply to farmers in a more sustainable way while taking affirmative action in favour of female headed households. Formal education and land entitlement should also be promoted to step up adoption of the improved technologies. Keywords: Adoption, Agricultural credit, Endogenous treatment, Poisson regression, Sustainable Agricultural Practices